A meta-analytic review of fish antioxidant defense and biotransformation systems following pesticide exposure. (March 2022) - Santana, Manuela S.; Domingues de Melo, Gabriel; Sandrini-Neto, Leonardo; Di Domenico, Maikon; Prodocimo, Maritana Mela
Abstract: Pesticides reach aquatic ecosystems and interact with various targets in cells of fish and other living organisms. Toxicity originates during the metabolization process, which may produce toxic metabolites or reactive oxygen species (ROS). Ethoxyresorufin- O -deethylase (EROD), glutathione S-transferase (GST), catalase (CAT), superoxide dismutase (SOD) activities, and levels of reduced glutathione (GSH) indicate toxicants interacted with drug-metabolizing and antioxidant systems, i.e., they are biomarkers of biotransformation and oxidative stress. We meta-analytically quantified the impact of pesticides on the mean response and variability of these biomarkers. Our goals were to verify ( i ) the overall effect of pesticides on oxidative stress and biotransformation, and how each biomarker respond to exposure; ( ii ) how the life stage of fish (juvenile and adult) influence biomarkers variability and mean activity; ( iii ) to what extent fish sex (male, female or mixed-sex groups) modify pesticides toxicity; ( iv ) how different classes of pesticides, and the combination of their concentration and time of exposure, affect each biomarker. Overall, pesticides induced oxidative stress and the biotransformation system. Regardless of life stage, EROD mean activity increased significantly. In exposed juveniles, CAT and GST variability decreased and increased, respectively. CAT mean activity was higher in females, while EROD and GST activities increased in males after pesticide exposure. Organophosphorus (OPs) and organochlorine insecticides, along with imidazole and triazole fungicides, affected biomarkers the most, however the combined effect of concentration and time of exposure of OPs was not detected. Notably, imidazoles and triazoles classes increased EROD by more than 100%. Additionally, we identified research gaps, such as the lack of effect estimates of relevant pesticides on EROD (e.g., pyrethroids and neonicotinoids) and the small number of studies evaluating GSH on female fish. Future researchers may use these gaps as a guide towards enhanced experimental designs and, consequently, a better understanding of pesticide toxic effects on fish. Graphical abstract: Image 1 Highlights: We conducted a meta-analysis of fish biomarker responses to pesticide exposure. Pesticides strongly affected antioxidant defense and biotransformation systems. Pesticides significantly increased EROD activity both in adult and juvenile fish. A decrease in CAT variability was observed in juvenile fish following exposure. Organophosphorus and organochlorine insecticides affected most biomarkers analyzed.